Daños y métodos de control de Trips en el cultivo de aguacate Persea americana - Game López, Ronaldo Alexi (2023)
This research describes the damage and control methods of Thrips in the Persea Americana avocado crop. Describe the symptoms caused by thrips in the avocado crop and mention the control measures adopted for thrips in said crop. Information was obtained from various scientific sources to prepare the document. Avocado is a fruit rich in lipids, which makes it a high-calorie option from a nutritional point of view. In addition, trips are one of the harmful organisms that affect your crop. Insects have a wide global distribution and cause damage through nutritional bites in plants and fruits, and they also transmit viruses. Saliva and toxins from travel harden and atrophy the limbus. Damage to young stems is manifested by elongated and irregularly shaped growth. Attack by nymphs and adults during flowering causes flower abortion, which reduces production. Trips damage avocado leaves and fruits by feeding on the cells of the epidermis, causing pale or brown areas that can allow the entry of pathogenic microorganisms. Options are necessary to manage this insect when populations are high, such as cultural, chemical and biological control.